2018
DOI: 10.14431/aw.2018.09.34.3.29
|View full text |Cite
|
Sign up to set email alerts
|

How Does Spousal Support Affect Women’s Quality of Life in the Postpartum Period in Turkish Culture?

Abstract: Bireyler çevrelerinde güvenebilecekleri, kendileriyle ilgilenen, değer veren ve onları seven kişilerin varlığını hissettiklerinde bir sosyal destek sistemi içinde bulundukları kabul edilir. Aile üyeleri yaşam boyu birey için en önemli kişisel destek kaynaklarıdır. Aile içerisindeki ilişkiler daha da özelleştirildiğinde bir başka deyişle sadece evlilik ilişkisi incelendiğinde eşler çoğunlukla destek sağlayan kişiler olarak diğer sosyal destek kaynaklarına oranla ayrı bir önem kazanmaktadır. Eşlerin birbirlerind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 15 publications
3
17
0
4
Order By: Relevance
“… 37 Higher relationship satisfaction is likely to be related to women’s assessments of better spousal social, economic and emotional support in the postpartum period, factors known to be associated with higher HrQoL overall. 24 26 38–40 Better spousal support has been shown to lead to reductions in stress, anxiety during pregnancy, childbirth and in the postpartum period, offsetting some of the challenges of coping with parenthood and child care. 26 In our study, we defined relationship satisfaction in relation to shared decision making, agreement on key family issues and communication between the couples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 37 Higher relationship satisfaction is likely to be related to women’s assessments of better spousal social, economic and emotional support in the postpartum period, factors known to be associated with higher HrQoL overall. 24 26 38–40 Better spousal support has been shown to lead to reductions in stress, anxiety during pregnancy, childbirth and in the postpartum period, offsetting some of the challenges of coping with parenthood and child care. 26 In our study, we defined relationship satisfaction in relation to shared decision making, agreement on key family issues and communication between the couples.…”
Section: Discussionmentioning
confidence: 99%
“…Couples who frequently discuss, agree and make joint decisions on key family issues are likely to support each other to achieve their desired targets and thus have a higher HrQoL than those who do not. 24 25 Increased spousal support may be responsible for the observed association between better relationship scores with HrQoL. However, women in Burkina Faso typically receive support from their extended family and social network, often in the form of financial and other assistance (such as helping in the care of the newborn) following childbirth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A former study showed that socio-emotional help and support were among the significant predictors of depression, stress, and QOL among pregnant women (43). Another study reported a significant positive relationship between postpartum QOL and husband's support (44). Similarly, a study found that spousal support and good marital relationship were significant factors contributing to the improvement of postpartum QOL (44).…”
Section: Discussionmentioning
confidence: 99%